2019
DOI: 10.1177/0973005219870271
|View full text |Cite
|
Sign up to set email alerts
|

Is Crop Insurance Creating Welfare Gain in North-east China? How to Improve Policy Implementation?

Abstract: The article evaluates the expected welfare gain from voluntary partial government-subsidized maize insurance in north-east China. A total of 356 maize-growing households’ risk preferences from Linkou County of Heilongjiang province are examined and their expected welfare gains were analysed by the expected utility theory with each farmer’s unique risk preference. The research found that 217 out of 356 households are rational decision-makers and most of them are risk averse. In term of expected welfare gain, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Two studies mentioned the provision of incentives as cause to moral hazard behavior in the agriculture sector. Paper P23 (Le et al 2020) studied the occurrence of moral hazard related to government-subsidized crop insurance in Northeast China. The results showed that crop insurance triggered hazard behavior among farmers because they were more inclined to care less regarding herbicides and fertilizers used for their crops.…”
Section: Incentives/carrot Approachmentioning
confidence: 99%
“…Two studies mentioned the provision of incentives as cause to moral hazard behavior in the agriculture sector. Paper P23 (Le et al 2020) studied the occurrence of moral hazard related to government-subsidized crop insurance in Northeast China. The results showed that crop insurance triggered hazard behavior among farmers because they were more inclined to care less regarding herbicides and fertilizers used for their crops.…”
Section: Incentives/carrot Approachmentioning
confidence: 99%
“…In a household survey, researchers found that among 365 households engaged in agricultural production, only 60 % make rational decisions and are not at risk. Scientists state that only obtaining of additional education, including new knowledge about unforeseen risks, will allow increasing farmers' incomes by 55 % from growing crops [3]. U.S. researchers 5 consider that the review of agricultural insurance research conducted by them will help insurance companies create new insurance products for the agricultural sector and government, and also will help governments in many countries make rational decisions about their provision [5].…”
mentioning
confidence: 99%